The effects of replacing soybean meeal with dried distillers grains with solubles in Boer goats - Zurschmiede, Josephine M.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Internationally, the meat goat industry has been increasing. A census calculated that the goat population intended for meat purposes went up one hundred million in just ten years worldwide (FAOSTAT 2002 and 2012). In the United States, there is very limited research on goat nutrition for maximum performance. The objective of this experiment is to collect data concerning if soybean meal(SBM) can be replaced with varying amounts of dried distillers grains with solubles(DDGS) in Boer goat diets. Our hypothesis is that up to 66% of SBM can be replaced with DDGS in Boer goat diets without compromising growth performance or meat characteristic. 48 Boer goats (approximately 70 d of age) went through a 14 day step up period before they were allocated to one of four treatments in a completely randomized design. The four treatments fed were of differing percentages of DDGS replacing SBM: 1) 0% DDGS, 2) 33% DDGS, 3) 66% DDGS, 4) 100% DDGS. Goats were organized by placing three kids per pen and four pens per treatment with pen as the experimental unit. Average daily gain (ADG), average daily feed intake (ADFI), and gain to feed ratio (GF) was calculated every two weeks over the 47 day feeding period. After the 47 days, 2 out of 3 goats per pen were slaughtered and carcass characteristics such as hot carcass weight (HCW), loin eye area (LEA) and % carcass yield were collected. Data will be analyzed using the GLIMMIX procedure of SAS (SAS Inst., Cary, NC). The model will include effects of the level of DDGS with P-value ≤ 0.05 considered significant. LS Means will be utilized to partition treatment differences (P < 0.05). The results concluded that there was no significant difference in ADG, ADFI, HCW, LEA, or % carcass yield between treatments. The linear P values were (P=0.017), (P=0.737), (P=0.262), (P=0.183), and (P=0.737) respectively. The results fail to reject the null hypothesis. Up to 100% of SBM can be replaced with DDGS without impacting growth performance.
Keywords: Spring 2018